Macroeconomics Variables and the Stock Market : The Case of Russia - Yelyubayev, Talgat (2011)
This study investigates the relationship between macroeconomic variables and the Russian stock market. Following macroeconomic variables are used: industrial production, consumer price index, discount rate, exchange rate and oil prices. Index of the MICEX stock exchange is chosen to represent the Russian market. Monthly time series data of mentioned variables are used and time span covers September 1997 to April 2011 period. Empirical analysis consists of applying Augmented Dickey-Fuller (ADF), Phillips-Perron (PP) and Kwiatkowski-Phillips-Schmidt-Shin (KPSS) tests to identify stationarity of variables; Johansen multivariate cointegration test to establish long-run relations; vector error correction model (VECM) to analyze short-run relations and Granger causality. ADF and PP tests reveal conflicting results, however, KPSS shows that variables have one unit root. Johansen test illustrates long-run relationship between the Russian stock market and five macroeconomic variables. Moreover, the first normalized equation indicates positive significant long-run connection between stock prices and industrial production, exchange rate and discount rate. On the other hand, stock prices respond negatively to consumer price index. Long-run linkage among stock and oil prices are also positive, but insignificant. VECM shows that coefficients of MICEX with respect to the first error correction term is negative, however, it is insignificant. On contrary, values of MICEX in the second error correction term are positive and significant. In Granger causality sense, MICEX has bidirectional long-run causal linkages with all variables except for exchange rate. In the short-run feedback relations are found with all variables except for industrial production. This means that the Russian stock market can be considered as the leading indicator of the Russian economy. Furthermore, the evidence of cointegration and causality implies that the Russian market is inefficient.